2005
DOI: 10.1063/1.1940139
|View full text |Cite
|
Sign up to set email alerts
|

Raman-scattering study of the InGaN alloy over the whole composition range

Abstract: We present Raman-scattering measurements on InxGa1−xN over the entire composition range of the alloy. The frequencies of the A1(LO) and E2 modes are reported and show a good agreement with the one-mode behavior dispersion predicted by the modified random-element isodisplacement model. The A1(LO) mode displays a high intensity relative to the E2 mode due to resonant enhancement. For above band-gap excitation, the A1(LO) peak displays frequency shifts as a function of the excitation energy due to selective excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
60
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 32 publications
10
60
0
2
Order By: Relevance
“…This corresponds to longitudinal optical ͑LO͒ modes of the InGaN alloy, which are resonantly enhanced via the Fröhlich interaction under the near resonant conditions of the experiment. 38 No feature associated with the E 2 mode could be observed above the luminescence background. Although the experiments were carried out in backscattering configuration from the sample surface, given the morphology of the NWs ͑see Fig.…”
Section: B Optical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This corresponds to longitudinal optical ͑LO͒ modes of the InGaN alloy, which are resonantly enhanced via the Fröhlich interaction under the near resonant conditions of the experiment. 38 No feature associated with the E 2 mode could be observed above the luminescence background. Although the experiments were carried out in backscattering configuration from the sample surface, given the morphology of the NWs ͑see Fig.…”
Section: B Optical Propertiesmentioning
confidence: 99%
“…This probably reflects In composition fluctuations across the NWs ͑see above͒ and also within the ensemble of NWs probed by the Raman measurement. 38 The LO peak of the InGaN/GaN NW heterostructure is clearly shifted to lower frequencies relative to that of the InGaN NW sample. Such a frequency shift could be related to a higher In content of the InGaN alloy in the NW heterostructure.…”
Section: B Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such deviations are usually attributed to the strain of the samples. 12,20 However, many authors have shown that the A 1 (LO) frequency strongly depends on the excitation wavelength and/or on temperature, and different effects have been invoked to explain the observations: i) strain and/or compositional gradients over depth; 13,19 ii) compositional inhomogeneities giving rise to selective resonant excitation of domains with a particular In content; 5,7,15,17 iii) relaxation of the wave-vector selection rule. 18 Thus, it remains necessary to identify which mechanisms are actually playing a key role in the behavior of the A 1 (LO) mode of InGaN.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been devoted to study the vibrational properties of hexagonal InGaN thin films [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and InGaN/GaN quantum wells. [22][23][24] Although it is well accepted that both the A 1 (LO) and the E 2h phonon modes of InGaN display a one-mode behavior, 15,16 there are still open questions regarding the behavior of the optical phonons in the InGaN alloy. While the modified random-element isodisplacement (MREI) model 25 predicts that the frequency of both modes varies linearly from those of the two binary endmembers (GaN and InN), some authors have measured E 2h frequencies that seem to exhibit a significant bowing in relation to the linear frequency dependence.…”
Section: Introductionmentioning
confidence: 99%